First year medical student stress and coping in a problem-based learning medical curriculum - Moffat, Katrina J; McConnachie, Alex; Ross, Sue; Morrison, Jillian M (Medical education, 2004)
Objective  To examine the prevalence of psychological morbidity, sources of stress and coping mechanisms in first year students in a problem‐based learning undergraduate medical curriculum. Design  Longitudinal cohort questionnaire survey. Setting  Glasgow University Medical School. Participants  All first year students (n = 275) in the 1997–98 intake. Main outcome measures  Scores on the 12‐item General Health Questionnaire (GHQ‐12), sources of stress and coping strategies. Results  The prevalence of psychological morbidity and mean GHQ‐12 scores increased significantly between term 1 and term 3, with no significant gender differences. Principal stressors were related to medical training rather than to personal problems, in particular uncertainty about individual study behaviour, progress and aptitude, with specific concerns about assessment and the availability of learning materials. The group learning environment, including tutor performance, and interactions with peers and patients caused little stress. Students generally used active coping strategies. Both stressor group scoring and coping strategies showed some variation with gender and GHQ caseness. Conclusions  Increased student feedback and guidance about progress throughout the year and the provision of adequate learning resources may reduce student stress. Educational or pastoral intervention regarding effective coping strategies may also be beneficial. Continued follow‐up of this cohort could provide information to inform further curriculum development and, if appropriate, aid the design of programmes for the prevention of stress‐related problems.